Monsoon intensification in East Asia triggered the evolution of its flora - Ye, Jun-Wei; Tian, Bin; Li, De-Zhu (Frontiers in Plant Science, 2022)
East Asia (EA), falls with the region of Asian monsoon that is composed of East Asia monsoon (EAM) and Indian monsoon (IM), is known for its high species diversity and endemism. Qian and Ricklefs (2000) attributed this to extreme physiographical heterogeneity in conjunction with climate and sea-level changes during the Pleistocene; this hypothesis has been widely proven by phylogeographic studies. Recently, dated phylogenies have indicated that the origins (stem age) of the flora occurred after the Oligocene-Miocene boundary and are related to the establishment of the EAM. Hence, this study further examined whether the strengthening of the monsoons triggered floral evolution via meta-analysis of tempo-spatial pattern of evolutionary radiation dates (crown ages) of 101 endemic seed plant genera. Taxonomic diversification began during the late Eocene, whereas accumulated number of diversifications did not significantly accelerate until late Miocene. Distribution of weighed mean and average divergence times in EAM, IM or transitional regions all fall within mid-late Miocene. Fossils of tertiary relict genera are mostly widely distributed outside EA and only half of them are firstly found in EA during the Miocene, while their divergence times are mostly after late Miocene. Pattern of divergence time of monotypic and polytypic genera reflect influence of climatic change after late Pliocene exert more influence on monotypic genera. The two key stages of floral evolution coincide with intensifications of EAM and IM, especially the summer monsoon which brings humid climate. Integrated review of previous studies concerning flora, genus, and species levels further support our suggestion that monsoon intensification in EA triggered evolution of its flora.